2004
DOI: 10.1074/jbc.m400029200
|View full text |Cite
|
Sign up to set email alerts
|

Physical Interaction between Replication Protein A and Rad51 Promotes Exchange on Single-stranded DNA

Abstract: Replication protein A (RPA) is displaced from singlestranded DNA (ssDNA) by Rad51 during the initiation of homologous recombination. Interactions between these proteins have been reported, but the functional significance of the direct RPA-Rad51 interaction has yet to be elucidated. We have identified and characterized the interaction between DNA-binding domain A of RPA (RPA70A) and the N-terminal domain of Rad51 (Rad51N). NMR chemical shift mapping showed that Rad51N binds to the ssDNA-binding site of RPA70A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 39 publications
(59 reference statements)
6
93
1
2
Order By: Relevance
“…A key enzyme in HR is Rad51, which forms a presynaptic complex on ssDNA and mediates strand exchange reactions (17,19,20). Importantly, it was shown that both Rad51 and Rad52 preferentially associate with hyperphosphorylated RPA2 (46).…”
Section: Rfwd3 Localizes To Sites Of Dna Damage-previouslymentioning
confidence: 99%
See 1 more Smart Citation
“…A key enzyme in HR is Rad51, which forms a presynaptic complex on ssDNA and mediates strand exchange reactions (17,19,20). Importantly, it was shown that both Rad51 and Rad52 preferentially associate with hyperphosphorylated RPA2 (46).…”
Section: Rfwd3 Localizes To Sites Of Dna Damage-previouslymentioning
confidence: 99%
“…RPA is also shown to be directly involved in homology-directed repair. RPA interacts with homologous recombination (HR) repair protein Rad51, Rad52, and BRCA2 (15)(16)(17)(18)(19)(20)(21)(22)(23). Depletion of RPA by siRNA knockdown impairs the recruitment of Rad51 to sites of DNA repair and increases sensitivity to DNA damaging agents (18,24).…”
mentioning
confidence: 99%
“…Although the exact role of Mcm10 in replication initiation has yet to be elucidated, it is reasonable to envision Mcm10 as a macromolecular recruiting and/or scaffolding protein because of the fact that Mcm10 contains two domains that can bind to DNA and pol ␣ (29). This follows a common strategy for numerous modular proteins involved in DNA processing; there is a significant kinetic advantage to deconstructing protein interactions into two or more weak binding sites (68). The recruitment of pol ␣ to origins of replication by Mcm10 would be a significant step to signal nascent DNA synthesis and contribute to fork stability (6,12,16,24,26,27,29,71).…”
Section: A Molecular Mechanism For Mcm10mentioning
confidence: 99%
“…2A). Rad51 also interacts with both RPA1 and RPA2 (30,46). To explore domains involved in the altered interactions, we also examined interactions with a mutant form of RPA1 composed solely of two copies of a fragment of the core DNA binding domain, AA-His (containing residues 177-303 of RPA1) (47).…”
Section: Rpa4 Mrna Is Found In Normal Humanmentioning
confidence: 99%